The Syphilis Pandemic Prior to Penicillin: Origin, Health Issues, Cultural Representation and Ethical Challenges - Lisa Ekselius; Bengt Gerdin; Anders Vahlquist (Medical Journals Sweden, 2024)
Syphilis is currently a treatable disease, with a low incidence in most developed countries, although the prevalence has increased recently, especially among men-who-have-sex-with-men. In many of the least developed countries, however, syphilis is still a major health problem, although the problem is not comparable to the desperate situation worldwide less than 80 years ago. At that time, and for many centuries previously, syphilis dramatically affected the lives and health of individuals and threatened the well-being of many societies. This review examines the aetiology, transmission, and many manifestations of syphilis from a historical perspective, emphasizing morbidity, treatment, psychosocial and cultural manifestations, as well as ethical issues uncovered in the clinical search for knowledge about the manifestations of the disease.